Argentina's business cycles in the long run: A descriptive exercise (1880-2020) - Catelén, Ana Laura (2023)
An updated descriptive analysis of the cyclical behavior of the main macroeconomic variables in Argentina between 1880 and 2020 suggests that the dynamics changed substantially since 1976. Specifically, we observed changes in the phases’ duration, amplitude, and excess and that economic volatility did decrease when the economy was relatively more closed between 1945 and 1976 but it increased again until 2020.